The Effects of Allopurinol on Glutathione Sulfhydryl (GSH) Serum Level, Six Minute Walking Test, and CAT Score of COPD Patients - Samuel Samuel; Suradi Suradi; Yusup Subagio Sutanto (Jurnal Respirologi Indonesia, 2019)
Background: Stress oxidative in COPD impairs striated muscle thus worsening COPD symptoms. Allopurinol as antioxidant reduces stress oxidative so it can improve exercise capacity and clinical symptoms. The aims of this study were to analyze the effects of allopurinol on GSH serum level, six minute walking test (6MWT), and COPD assessment test (CAT) score of COPD patients. Methods: This study was a pre and post test clinical trial held in pulmonology outpatient clinic in Dr. Moewardi General Hospital Surakarta from January to February 2018 using purposive sampling. The COPD group C and D patients were cathegorized as intervention group which received allopurinol 300 mg/day for 4 weeks and control group which did not receive allopurinol. Glutathione sulfhydryl serum level, 6MWT, and CAT score were measured at baseline and after 4 weeks in both groups. Results: A total of 37 stable COPD group C and D patients were included in this study. The intervention group showed decreased GSH level (52.58±38.39) µg/ml and CAT score (10.37±4.46) which were statistically significant compared to control group (P